2021
DOI: 10.2147/phmt.s326319
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Partial Immunization Among Children Aged 12–23 Months in Yirga Cheffe District, South Ethiopia – A Community-Based Unmatched Case-Control Study

Abstract: Background: Universal age-specific immunization is one of the areas where preventive public health policy has become successful. Despite the increase in global immunization coverage, however, many children around the world, especially in developing countries, are still left unvaccinated. The study aimed at assessing the determinants of partial immunization among children 12-23 months of age in Yirga Cheffe, Gedeo, Ethiopia. Methodology: A community-based unmatched case-control study design was conducted. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…The possible justification is that mothers who did not receive information or were not exposed to vaccination may not know the significance of vaccination, resulting in a lack of knowledge and, as a result, their children may be partially vaccinated. Children of unvaccinated mothers were more likely to be partially vaccinated, according to the evidence [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possible justification is that mothers who did not receive information or were not exposed to vaccination may not know the significance of vaccination, resulting in a lack of knowledge and, as a result, their children may be partially vaccinated. Children of unvaccinated mothers were more likely to be partially vaccinated, according to the evidence [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent report from Ethiopia, only 43% of children aged 12 to 23 months were completely vaccinated and 19% were unvaccinated [ 10 ]. In addition, another study found that 46 percent of children were only partially immunized [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vaccination is the process of inducing a protective response in an individual's body against a speci c illness by administering vaccines and one of the most cost-effective global public health interventions to reduce childhood morbidity and mortality (1,2). Defaulter to full vaccination is a condition in which a child missed routine vaccination schedule and not become fully vaccinated for any reasons that can put children at greater risk of acquiring vaccine-preventable diseases (3,4). Partial child vaccination against vaccine-preventable diseases is a signi cant public health challenge in developing countries and still in presence of vaccination, the children die by vaccine-preventable disease every year in developing countries (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Partial child vaccination against vaccine-preventable diseases is a signi cant public health challenge in developing countries and still in presence of vaccination, the children die by vaccine-preventable disease every year in developing countries (5,6). Expanding universal age-speci c immunization program is one of the areas where preventive public health policy has become successful (3). Currently, the EPI has emerged as highly effective and e cient method to improve child survival and the program's interventions led to the notable reduction in vaccine-preventable diseases worldwide (3,7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation